Queensland Kanaka Mission Solomon Island Branch - Dibley, W.H. (1904)
Letter of intention, to set up Solomon Islands Branch of the Queensland Kanaka Mission due to the intended compulsory deportation of Solomon Islanders form Australia to the Solomon Islanders.
Keywords: Queensland Kanaka Mission Solomon Island Branch; Brethren movement -- missions -- Australia -- history